Toxicity effects of caffeine in ICR mice prior to anti-malarial studys - Noriman, Ahmad Zakwan; Wan Hanafi, Wan Nurhayati; Basir, Rusliza; Agustar, Hani Kartini; Mohd Abd Razak, Mohd Ridzuan; Mohd Hassan, Wan Rozianoor (Atlantis Press International BV, 2024)
Caffeine is a stimulant that increase alertness in the body. However, little is known on the toxicity effects of caffeine in ICR mice. This study aimed to identify the toxicity effects of caffeine in ICR mice for further anti-malarial investigation. Adult ICR mice were injected with caffeine (5, 10, 20 mg/kg) for four days via intraperitoneal injection (i.p.) and were monitored for 30 days. All doses exhibited no changes in body temperature, locomotor activity and urine colour when compared to control mice. Besides that, there were no signs of piloerection and lethargic whereas the mice body weight kept increasing in 30 days of monitoring. Therefore, the treatment of caffeine with 5, 10 and 20 mg/kg b.w. in ICR mice exhibited no toxicity signs and can be used for further anti-malarial study.